TFE3 activation in a TSC1‐altered malignant PEComa: challenging the dichotomy of the underlying pathogenic mechanisms. (12th November 2020) - Schmiester, Maren; Dolnik, Anna; Kornak, Uwe; Pfitzner, Berit; Hummel, Michael; Treue, Denise; Hartmann, Arndt; Agaimy, Abbas; Weyerer, Veronika; Lekaj, Anja; Brakemeier, Susanne; Peters, Robert; et al.
Abstract: Perivascular epithelioid cell tumors (PEComas) form a family of rare mesenchymal neoplasms that typically display myomelanocytic differentiation. Upregulation of mTOR signaling due the inactivation of TSC1/2 (Tuberous Sclerosis 1 and 2) is believed to be a key oncogenic driver in this disease . Recently, a subgroup of PEComas harboring TFE3 ( Transcription Factor E3 ) rearrangements and presenting with a distinctive morphology has been identified. TSC1/2 and TFE3 aberrations are deemed to be mutually exclusive in PEComa, with two different pathogenic mechanisms assumed to lead to tumorigenesis. Here, we challenge this dichotomy by presenting a case of a clinically aggressive TCS1 ‐mutated PEComa displaying a TFE3 ‐altered phenotype. FISH analysis was suggestive of a TFE3 inversion; however, RNA and whole genome sequencing was ultimately unable to identify a fusion involving the gene. However, a copy number increase of the chromosomal region encompassing TFE3 was detected and transcriptome analysis confirmed upregulation of TFE3, which was also seen at the protein level. Therefore, we believe that the TSC1/2‐mTOR pathway and TFE3 overexpression can simultaneously contribute to tumorigenesis in PEComa. Our comprehensive genetic analyses add to the understanding of the complex pathogenic mechanisms underlying PEComa and harbor insights for clinical treatment options.